2013
DOI: 10.1194/jlr.m033415
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 mediates the lipid metabolism response to amino acid starvation

Abstract: This article is available online at http://www.jlr.org tissue (WAT), brown adipose tissue (BAT), skeletal muscle, and pancreas ( 3-6 ). FGF21 expression in liver is under tight control by peroxisome proliferator-activated receptor (PPAR) ␣ ( 7-10 ). It is induced in the liver during fasting and its expression induces a metabolic state that mimics long-term fasting. Thus, FGF21 is critical for the induction of hepatic fat oxidation, ketogenesis, and gluconeogenesis, which are metabolic processes critical for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 41 publications
1
91
2
Order By: Relevance
“…Furthermore, hepatic FGF21-mediated thermogenesis has also been described in response to maternal milk consumption in neonatal pups [35], and also in situations of metabolic stress, for example upon amino acid restriction [20]. These observations suggest that the hepatic FGF21-mediated increase in thermogenic capacity is an adaptive response to metabolic stress.…”
Section: Brown Adipose Tissue: Fgf21 Induces Thermogenic Capacitymentioning
confidence: 68%
See 3 more Smart Citations
“…Furthermore, hepatic FGF21-mediated thermogenesis has also been described in response to maternal milk consumption in neonatal pups [35], and also in situations of metabolic stress, for example upon amino acid restriction [20]. These observations suggest that the hepatic FGF21-mediated increase in thermogenic capacity is an adaptive response to metabolic stress.…”
Section: Brown Adipose Tissue: Fgf21 Induces Thermogenic Capacitymentioning
confidence: 68%
“…In WAT, it decreases FAS activity and the expression of lipogenic genes and increases the expression of FAO genes. Finally, there is an induction of UCP1 expression in BAT [20,100,101]. In contrast, in Fgf21-deficient mice this metabolic response to leucine is impaired, thus indicating that FGF21 is a key hormone in the regulation of lipid metabolism during leucine deprivation [20,81].…”
Section: Amino Acid-deficient and Low-protein Diets Increase Energy Ementioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that FGF21 gene expression is directly regulated by ATF4 (7,8,12,22) and potentially XBP-1 (9). A previous study reported that FGF21 repressed ER stress by inhibiting phosphorylation of eIF2a, an upstream activating factor of ATF4 (9).…”
Section: Discussionmentioning
confidence: 99%